The analgesic effects of newly developed magnetic stimulator in volunteers with shoulder stiffness - Yamamoto, Satoru; Nishi, Mitsuharu; Kakeda, Takahiro; Sasaki, Hironori; Ishikawa, Kozo; Ida, Yuika; Yoshida, Mitsuhiro; Ishikawa, Toshizo; Kishishita, Yusuke; Sumikawa, Yasuhiro; Yasuda, Seiko (PAIN RESEARCH, 2011)
We have newly developed a low-powered magnetic stimulator (MS) that is characterized by two different frequency modes: 2 kHz (low frequency) and 83 MHz (ultra-short wave). It is suggested that MS reduces rat neuropathic pain associated with the prevention of neuronal degeneration. However, little is known about certain mechanisms of MS, at least, applicable value of the analgesic approaches in clinical situation. Thus, we aimed to determine the analgesic effects of MS in human with shoulder stiffness. 　We recruited volunteers with shoulder stiffness (MS was applied once for 10 min.) and with acute pain (MS was applied once a day (10 min period) for 9 days. The trial study on analgesic effects in human of new magnetic therapeutic instrument (Angel Touch®) were examined. We examined safety of MS based on electrocardiographic testing and body surface temperature. By using the heart rate on the electrocardiogram, we used FFT analyzer to analyze low frequency components (LH: 0.05 - 0.15Hz) and high frequency components (HF: 0.15 - 0.45 Hz). Muscle shoulder stiffness has been improved by the continued irradiation without a thermal action. 　Based on the present study, we suggest that MS has beneficial analgesic effects in human, and that MS will be a useful approach to treatment for neurodegenerative disorder because it may relieve pain via improvement of functional modulation of pain-emotional system.